Carbon capture and storage across fuels and sectors in energy system transformation pathways. (February 2017) - Muratori, Matteo; Kheshgi, Haroon; Mignone, Bryan; Clarke, Leon; McJeon, Haewon; Edmonds, Jae
Highlights: CCS is a key mitigation option applicable to fossil and biomass primary energy. CCS has large mitigation potential in electricity and biofuels production sectors. Amount and application of CCS varies between integrated assessment models. CCS deployment across sectors and fuels depends on technology cost assumptions. Bioenergy deployment predominantly includes CCS in GCAM mitigation scenarios. Abstract: Carbon capture and storage (CCS) is broadly understood to be a key mitigation technology, yet modeling analyses provide different results regarding the applications in which it might be used most effectively. Here we use the Global Change Assessment Model (GCAM) to explore the sensitivity of CCS deployment across sectors and fuels to future technology cost assumptions. We find that CCS is deployed preferentially in electricity generation or in liquid fuels production, depending on CCS and biofuels production cost assumptions. We consistently find significant deployment across both sectors in all of the scenarios considered here, with bioenergy with CCS (BECCS) often the dominant application. As such, this study challenges the view that CCS will primarily be coupled with power plants and used mainly in conjunction with fossil fuels, and suggests greater focus on practical implications of significant CCS and BECCS deployment to inform energy system transformation scenarios over the 21st century.